Low Power Internet of Things Gateway - Kadioglu, Tevfik; Yildiz, Nerhun; Cesur, Evren (IEEE, 2016)
In this paper, the hardware and software development of a gateway targeting Internet of Things applications is disclosed and a new UDP based sensor network communication model for the reduction of network traffic and power consumption is proposed. On the other hand, various information about Internet of Things, wireless sensor networks and Contiki operating system are also given throughout the paper.
Keywords: Internet-of-Things; gateway; low-power consumption; Contiki; 6LoWPAN; 6lbr; Engineering